Therapeutic options in Alzheimer''s disease. (June 2006) - Moreira, Paula I; Zhu, Xiongwei; Nunomura, Akihiko; Smith, Mark A; Perry, George
Alzheimer''s disease (AD) places an enormous burden on individuals, families and society. Consequently, a tremendous effort is being devoted to the development of drugs that prevent or delay neurodegeneration. Current pharmacological treatments are based on the use of acetylcholinesterase inhibitors or memantine, a N -methyl-D-aspartate channel blocker. However, new therapeutic approaches, including those more closely targeted to the pathogenesis of the disease, are being developed. These potentially disease-modifying therapeutics include secretase inhibitors, cholesterol-lowering drugs, amyloid-ββ immunotherapy, nonsteroidal anti-inflammatory drugs, hormonal modulation and the use of antioxidants. The possibility that oxidative stress is a primary event in AD indicates that antioxidant-based therapies are perhaps the most promising weapons against this devastating neurodegenerative disorder.